2014
DOI: 10.1016/j.curtheres.2014.02.001
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Cactus Fiber on the Excretion of Dietary Fat in Healthy Subjects: A Double Blind, Randomized, Placebo-Controlled, Crossover Clinical Investigation

Abstract: BackgroundCactus (Opuntia ficus-indica) fiber was shown to promote weight loss in a 3-month clinical investigation. As demonstrated by in vitro studies, cactus fiber binds to dietary fat and its use results in reduced absorption, which in turn leads to reduced energy absorption and ultimately the reduction of body weight.ObjectiveThe objective of our study was to elucidate the dietary fat binding capacity of cactus fiber through determination of fecal fat excretion in healthy volunteers.Subjects and MethodsThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 27 publications
1
40
0
1
Order By: Relevance
“…Elbashir et al () also found hypoglycemic properties from inhibiting α‐glucosidases, contributing to overall diminishing of total body weight. Other explanations might concern oil absorption capacity (Thanatcha & Pranee, ) as indigestible polysaccharides can reduce fat absorption partly by binding to fat molecules and increasing their excretion (Uebelhack, Busch, Alt, Beah, & Chong, ); Though Deshpande et al () found tannins in related Ziziphus mauritana peel with the ability of inhibiting adipogenesis and of increasing adiponectin and PGC1α expression (both responsible for inducing lipid hydrolysis and fatty acid β‐oxidation), no report of tannins was found upon NabM, as more data are required.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elbashir et al () also found hypoglycemic properties from inhibiting α‐glucosidases, contributing to overall diminishing of total body weight. Other explanations might concern oil absorption capacity (Thanatcha & Pranee, ) as indigestible polysaccharides can reduce fat absorption partly by binding to fat molecules and increasing their excretion (Uebelhack, Busch, Alt, Beah, & Chong, ); Though Deshpande et al () found tannins in related Ziziphus mauritana peel with the ability of inhibiting adipogenesis and of increasing adiponectin and PGC1α expression (both responsible for inducing lipid hydrolysis and fatty acid β‐oxidation), no report of tannins was found upon NabM, as more data are required.…”
Section: Resultsmentioning
confidence: 99%
“…also found hypoglycemic properties from inhibiting α-glucosidases, contributing to overall diminishing of total body weight. Other explanations might concern oil absorption capacity(Thanatcha & Pranee, 2011) as indigestible polysaccharides can reduce fat absorption partly by binding to fat molecules and increasing their excretion(Uebelhack, Busch, Alt, Beah, & Chong, 2014); ThoughDeshpande et al (2013) found tannins in related Ziziphus mauritana peel with the ability of inhibiting adipogenesis and of increasing adiponectin and PGC1α expression (both responsible for inducing lipid hydrolysis and fatty acid β-oxidation), no report of tannins was found upon NabM, as more data are required.After 45 days, WPH also performed properly, decreasing significantly (p ≤ .05) TAGs to 95.88, 98.96, and 77.11 mg/dl (WPH, WPH-PHM, and WPH-NabM, respectively). The most significant decrease TA B L E 5 Initial and final body weight and liver weight of rats fed with milk protein-mucilage complexes…”
mentioning
confidence: 99%
“…Cactus fiber showed an increased fecal fat excretion compared with placebo. No adverse events were reported throughout the study period [20].…”
Section: Introductionmentioning
confidence: 93%
“…The betacyanins identified in Opuntia fruits include betanidin, betanin, isobetanin, isobetanidin, neobetanin, phyllocactin, and gomphrenin I [3, 4, 2426]. O. streptacantha (Cardona cultivar), (Rojalisa cultivar), and O. megacantha (Naranjona cultivar) contain traces of betanidin 5-O- β -sophoroside [34].…”
Section: Cladodes Chemical Compositionmentioning
confidence: 99%